2020
DOI: 10.1155/2020/8868245
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of COL17A1 Predicts Poor Prognosis and Promotes the Tumor Progression via NF-κB Pathway in Pancreatic Adenocarcinoma

Abstract: COL17A1 (collagen type XVII alpha 1 chain) is known to be upregulated and has a prognostic role in many malignancies, as well as contributing to cell proliferation, apoptosis, and invasion. However, little knowledge is available on the expression and prognostic value of COL17A1 in pancreatic adenocarcinoma (PDAC). In our study, we searched the public database and found that mRNA and protein levels of COL17A1 are commonly upregulated in PDAC tissues. The immunohistochemical analysis conducted by us revealed enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…To examine the effects of COL17A1 expression on tumorigenesis in vivo, we established two murine homograft tumor models in which KPC or AK4.4 cells were injected subcutaneously into syngeneic C57BL/6 or FVB mice (C57BL/6‐KPC and FVB‐AK4.4 models), respectively (Figure 3A). KPC‐Col17a1 cells formed larger tumors than did KPC‐vector cells in recipient C57BL/6 mice (Figure 3B–D), consistent with a recent finding that COL17A1 expression promoted the growth of tumors formed by the human pancreatic cancer cell line AsPC‐1 in immunodeficient nude mice 14 . In contrast, tumors formed by AK4.4‐Col17a1 cells were markedly smaller than those formed by AK4.4‐vector cells in recipient FVB mice (Figure 3E–G).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…To examine the effects of COL17A1 expression on tumorigenesis in vivo, we established two murine homograft tumor models in which KPC or AK4.4 cells were injected subcutaneously into syngeneic C57BL/6 or FVB mice (C57BL/6‐KPC and FVB‐AK4.4 models), respectively (Figure 3A). KPC‐Col17a1 cells formed larger tumors than did KPC‐vector cells in recipient C57BL/6 mice (Figure 3B–D), consistent with a recent finding that COL17A1 expression promoted the growth of tumors formed by the human pancreatic cancer cell line AsPC‐1 in immunodeficient nude mice 14 . In contrast, tumors formed by AK4.4‐Col17a1 cells were markedly smaller than those formed by AK4.4‐vector cells in recipient FVB mice (Figure 3E–G).…”
Section: Resultssupporting
confidence: 91%
“…expression in tumor tissue was associated with overall survival in PAAD and BRCA (Figure 1A,C), consistent with previous observations, 14,16 although this association was not significant for BRCA after Bonferroni correction for multiple testing. Of note, a higher COL17A1 mRNA abundance was associated with a worse or better overall survival for patients with PAAD or BRCA, respectively, suggesting that COL17A1 may have different roles in cancer progression depending on cancer type.…”
Section: Survival Analysis For Cancer Patients Revealed That Col17a1supporting
confidence: 91%
See 1 more Smart Citation
“…Dsg3 plays an oncogenic role in head neck cancer [53]. Col17a1 plays an essential role in many malignancies by contributing to cancer cell proliferation and invasion [54].…”
Section: Discussionmentioning
confidence: 99%
“…XVII collagen is an adhesion protein present in basal epithelial cells, encoded by COL17A1, that affects the growth and migration of cells [ 29 ]. COL17A1 is associated with poor prognosis in several tumors [ 30 , 31 ]. Pulari et al found that high expression and hypomethylation of COL17A1 were associated with poor prognosis in epithelial carcinoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%